2016
DOI: 10.1007/s12010-016-2077-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rol Genes on Polyphenols Biosynthesis in Artemisia annua and Their Effect on Antioxidant and Cytotoxic Potential of the Plant

Abstract: Flavonoids are famous for their antioxidant capacity and redox potential. They can combat with cell aging, lipid peroxidation, and cancer. In the present study, Artemisia annua hybrid (Hyb8001r) was subjected to qualitative and quantitative analysis of flavonoids through HPLC. Rol genes transgenics of A. annua were also evaluated for an increase in their flavonoid content along with an increase in antioxidant and cytotoxic potential. This was also correlated with the expression level of flavonoids biosynthetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
21
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 49 publications
6
21
0
1
Order By: Relevance
“…Our findings are supported by previous reports which demonstrated that rolB and C genes increased the amount of artemisinin and its derivatives in Artemisia annua by overexpressing the amorphadiene synthase (ADS), aldehyde dehydrogenase 1 (ALDH1), cytochrome P450, (CYP71AV1), PAL, cholane synthase (CHS), and trichomespecific fatty acyl-CoA reductase 1(TAFR1) genes (Dilshad et al, 2015(Dilshad et al, , 2016. Furthermore, Kayani et al (2016aKayani et al ( , 2017 found that rolABC-positive hairy root clones of A. bracteosa produce enhanced phytoecdysteroid content (up to 4449 μg g −1 ) compared to control hairy roots.…”
Section: Relative Gene Expression By Quantitative Real-time Pcrsupporting
confidence: 91%
“…Our findings are supported by previous reports which demonstrated that rolB and C genes increased the amount of artemisinin and its derivatives in Artemisia annua by overexpressing the amorphadiene synthase (ADS), aldehyde dehydrogenase 1 (ALDH1), cytochrome P450, (CYP71AV1), PAL, cholane synthase (CHS), and trichomespecific fatty acyl-CoA reductase 1(TAFR1) genes (Dilshad et al, 2015(Dilshad et al, , 2016. Furthermore, Kayani et al (2016aKayani et al ( , 2017 found that rolABC-positive hairy root clones of A. bracteosa produce enhanced phytoecdysteroid content (up to 4449 μg g −1 ) compared to control hairy roots.…”
Section: Relative Gene Expression By Quantitative Real-time Pcrsupporting
confidence: 91%
“…After dissection of rats, their midbrain region of CNS was dissected and washed thrice with cold saline and samples were quickly subjected to storage at −70 °C until estimation of dopamine and serotonin was done by HPLC as reported earlier [ 36 , 37 ]. Briefly, tissues were homogenized in phosphate buffer and then subjected to centrifugation at 14000 rpm for 10 min at 4 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Recently it was shown by Dilshad et al (2016) that transgenic plants of Artemisia annua carrying rol B gene demonstrated threefold increase in rutin and caffeic acid, sixfold increase in isoquercetin, and fourfold increase in quercetin as compared to the wild-type plants. They suggested that flavonoids content increase was caused by altering the expression level of the genes of flavonoids biosynthetic pathway.…”
Section: Resultsmentioning
confidence: 99%